2011
DOI: 10.14412/1996-7012-2011-651
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Diagnosis of Primary Osteoporosis

Abstract: Остеопороз (ОП) -системное заболевание скелета, ха-рактеризующееся снижением костной массы и нарушением микроархитектоники костной ткани, приводящее к увели-чению хрупкости кости и риска переломов.Общепринятой классификацией ОП в настоящее время является подразделение его на первичную и вторичную формы. Первичный ОП -самостоятельное заболевание, развивается в любом возрасте, однако более 80% больных -это женщины старше 50 лет. Вторичный ОП в большинстве случаев является симптомом других заболеваний или след-ст… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…The cortical index was calculated as follows [ 29 ]: 10 cm below the base of the lesser trochanter of the femoral bone, the total diameter of the bone diaphysis and the width of the medullary canal were measured. The difference between these two indicators corresponds to the total thickness of the cortical bone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cortical index was calculated as follows [ 29 ]: 10 cm below the base of the lesser trochanter of the femoral bone, the total diameter of the bone diaphysis and the width of the medullary canal were measured. The difference between these two indicators corresponds to the total thickness of the cortical bone.…”
Section: Resultsmentioning
confidence: 99%
“…The cortical thickness index in animals in the study groups on study day 21 was closer to the limits of the normal range, compared to this parameter in the control group. If the cortical thickness index is smaller than the normal value [ 29 ], it is fair to say that cortical bone thinning and calcium depletion has taken place. Hence, it has been demonstrated that the use of the supplements under study favorably affects calcium and phosphorus absorption from food and prevents bone decalcification during bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Клиническое исследование являлось ретроспективным, сравнительным, выполненным с включением данных медицинских карт амбулаторных пациентов с одной формой ОА коленных суставов II рентгенологической стадии по классификации Kellgren & Lawrence и согласно классификационным критериям ОА коленных суставов (ACR) [24], диагностическим критериям ОА коленных суставов, рекомендованным EULAR в 2010 г. [25].…”
Section: материалы и методы / Materials and Methodsunclassified